Model Kepemimpinan Situasional Kepala Sekolah dalam Meningkatkan Kinerja Guru (Studi Kasus di SDN 1 Tegalmunjul dan SDN 1 Munjuljaya) - Rina Nurhayati Setiani; Susanti Nurlestari; Suharyanto H. Soro; Ida Tejawiani (Global Education Journal, 2026)
Principal leadership is an important factor in improving teacher performance as an effort to achieve quality education. However, the reality in the field shows that principals often encounter teachers with varying levels of competence, experience, and motivation. Not all teachers require the same leadership treatment. This study aims to describe the application of the principal's situational leadership model in improving teacher performance. The researcher used a case study approach. Research respondents included principals, teachers, and education staff. Data collection methods through observation, interviews, and documentation, then analyzed using the Miles and Huberman model including data reduction, data presentation, and drawing conclusions. Data validity was tested through triangulation of sources and techniques. The results of the study indicate that (1) Principals apply a situational leadership model through four leadership styles, namely directing, coaching, supporting, and delegating, which are adjusted to the level of readiness, competence, and motivation of teachers; (2) The application of situational leadership appears to be able to improve work discipline, professional competence, motivation, responsibility, and the quality of learning carried out by teachers. The study can be concluded that the principal's situational leadership model can improve teacher performance if applied flexibly according to the level of maturity and needs of each teacher.